MÉTODO INTEGRADO PARA ANÁLISE DE EFICIÊNCIA ENERGÉTICA DE SISTEMAS CONSTRUTIVOS APLICADOS A RETROFIT DE EDIFICAÇÕES - Monteiro, Marcelo; Amorim, Claudia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The paper intends to demonstrate an integrated analysis method to select energy efficient building systems applied to office buildings, which will be intervened through the retrofit technique. The analyzes begin with the choice of materials and construction systems, considering that they are in line with the passive architecture of the building, followed by the measurement of the energy incorporated, the consumption and impact to the environment of these and the quantification of the end use of energy when implanted in the building. By means of the parametrization of the units of measure obtained in a single, the primary energy, will enable the reconfiguration of the constructive systems under analysis through the trade-off and chain management, thus producing, an integrated and refined analysis of the potential of the indicated constructive systems to be applied in the intervention, and is part of a doctoral thesis in development.